Use order of operations (PEMDAS)
<span>83-<span>(<span>59-<span>(<span>22-18</span>)</span></span>)
</span></span><span><span>83-<span>(<span>59-4</span>)
</span></span></span><span><span>83-55=</span></span>28
Final answer: 28
108 is the answer I’m pretty sure
-4x-2y = 16
2y = -4x-16
Get one variable alone on both equations
-4x - 16 = 2y
-4x - 16 = 2y
You'll realize that they're the same equation.
Use substitution
-4x-16 = -4x-16
0 = 0
x = all solutions
Use x = all solutions in an earlier equation to find y
-4x - 16 = 2y
SInce x can be all solutions y is also all solutions
y = all solutions
7. increasing; non-linear
8.A. y=4^x
9.A. y=6x
Answer: d^9
Step-by-step explanation: i dunno it is what it is